Salivary protein and some inorganic element levels in healthy children and their relationship to caries. - (:unkn) unknown (My University, 1994)
The levels of salivary proteins and some inorganic elements were measured in healthy children who were divided into 3 groups according to dentition. The study was prompted by the fact that there have been few studies on salivary composition and most of them have measured only a few components in children. Salivary protein was determined by the method of Lowry; protein electrophoresis carried out as described by Laemli; Na and K concentration was measured by flame photometry and Ca, Mg, Cl and P measured colorimetrically using Randox diagnostic kits. Significant differences were found between the groups for Mg, Na, total protein and some protein bands (obtained by electrophoresis). In all dentition groups, there was no significant difference in any of the levels between the children with and without caries. Salivary inorganic composition, total protein concentration and some protein bands rose linearly with age. Salivary protein and all the above inorganic element levels rose linearly with total caries surface area (Ds + ds), except for Mg which decreased linearly. Some of the protein bands decreased with Ds + ds.